LEGAL ANALYSIS OF THE CONSEQUENCES OF CANCELLATION OF LAND SALES DUE TO LEGAL DEFECTS FROM THE PERSPECTIVE OF PROTECTION OF THE RIGHTS OF THE PARTIES (RESEARCH STUDY AT THE NATIONAL LAND AGENCY OF BATAM CITY) - Farhan Juliando Jaswat; Erniyanti; Markus Gunawan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Land sale and purchase transactions are a form of agreement that plays an important role in the Indonesian agrarian legal system and requires legal certainty and protection for the parties involved. However, in practice, there are still many cases of land sale and purchase cancellations due to legal defects, such as document forgery, overlapping ownership, legal subject invalidity, or procedural violations. These legal defects not only harm the buyer and seller, but also give rise to liability for the notary as the maker of the authentic deed. This study aims to analyze the legal regulations, implementation, obstacles, and solutions related to the cancellation of land sales due to legal defects from the perspective of protecting the rights of the parties in notarial deeds. This study uses a normative juridical and empirical juridical approach. Data was obtained through a literature study of laws and regulations as well as field studies through interviews with notaries, land officials, and parties who had been involved in the cancellation of land sales in Batam City. The research was analyzed using positive law theory (John Austin), legal system theory (Lawrence M. Friedman), and legal certainty theory (Sudikno Mertokusumo). The results of the study show that although legal regulations are available in theory, the implementation of legal protection for the parties still faces serious challenges, especially in terms of the verification of document validity by notaries, the weak land administration system, and the lack of inter-agency integration. It is recommended that the government strengthen the digitization and supervision systems for notarial and land practices, as well as improve the legal literacy of the community in conducting land transactions so that legal protection can be guaranteed in a fair and proportional manner.